Templo do Bem : o Grupo Escolar de Uberaba, na escolarização republicana (1908 1918) - Guimarães, Rosângela Maria Castro (2007)
The aim of this research is a public primary school from Minas Gerais, named Grupo Escolar de Uberaba, the first institution of this kind in the city. It refers to a research in the field of the School Institutions History. The research hermeneutics admits some questioning about the historical identity of Grupo Escolar de Uberaba from 1908 to 1918, with the hypothesis that the school institution founded according to the republican ideals of the First Republic (positivism, nationalism, liberalism, laicity) was significant to a great part of the population from Uberaba as a form of propagation of these ideals which were in search of modernization and values such as order, progress, civility, public spirit, rationalization, hierarchy, hygienics. It was also the place of contradictional demonstrations of this period, some of them promoted by the republican moment itself and the others by the specific characteristics of the local society. The research was carried out from the following analysis categories: the motivation to found and install the Primary School, the spatial dimension (the shape and location of the school building), the students and teachers profile, as well as the school daily routine. The heuristics counted on the documents from the Minas Gerais Public Archive and the local press. The data obtained were interpreted from the revealed analysis categories with the special consideration of the reflexive relations between the private the Primary School, the city of Uberaba and, in general, the wider school historical context. The results obtained made the construction of a significant historical memory possible supporting the central subject and confirming the raised hypothesis. This school had historically constructed itself as a traditional teaching institution in Uberaba, still in activity. Due to the longevity of its existence through different moments of the Brazilian education, it would be interesting that other researches could be accomplished, regarding the other national historical moments. There is still a lot to be historically reconstructed besides the highlighted ten first years shown in this work.